Studies in the Vegetational History of Greenland, Palaeobotanical Investigations of some Holocene Lake and Bog deposits. - Fredskild, Bent (Meddelelser om Grønland, 1973)
The content of pollen in holocene, organic sediments in some Greenland lakes and bogs has been analyzed. The results are presented in relative and absolute diagrams. Furthermore, radiocarbon datings and macrofossil determinations are included in the description of the vegetational history. For the outer coast at Kap Farvel the first vegetation after the deglaciation around or shortly after 10,000 C" years B.P. was an open pioneer vegetation of widely distributed arctic plants. No southern species are proved. Snow-patches seem to have been frequent until ea. 7200 B.P., when Salix and Juniperus immigrated. A further amelioration is indicated around 5300 B.P. Betula glandulosa immigrates ea. 3800 B.P. The hypsithermal falls within 5300-2200 B.P. In the interior the sedimentation starts later. The vegetation was somewhat different due to the more continental climate, but the trend of the diagrams is parallel. Salix immigrates ea. 8000 B.P., Juniperus ea. 7000, Betula glandulosa between 4500 and 4000, and B.pubescens ea. 3600 B.P. The Norse settlement resulted in an opening of the scrubs and an increase in herbs, especially in the introduced strains of Rumex acetosella. The abandonment did not result in the extinction of the perennial "Norse plants". In the beginning the hydrophytes were common in the poor lakes at the outer coast, but oligotrophication soon made them very poor, and most species died out. At the head of Godthabsfjord, West Greenland, the vegetational development is parallel and presumably synchronous to that in the interior of South Greenland. In North Greenland the composition of the vegetation seems to have changed little in the past 5000 years, but in a period roughly between 4000-2100 B.P. and again between 1500 and 900 B.P. the climate seems to have been less arid. Exotic and long distance pollen is important in South Greenland sediments. Most common among the trees are Alnus, Picea and Pinus, but also herbs such as Ambrosia, Artemisia and Chenopodiaceae are frequent. Changes and differences in pollen and matrix sedimentation are discussed. At the outer coast 200-300, at the interior 1700-2700 pollen are sedimentated pr. cm2/yr. The average gyttja sedimentation is 3.1 cm/100 yr. The content of pollen in 31 recent gyttja samples is discussed.